Chitosan-PEO proton conducting polymer electrolyte membrane doped with NH 4NO 3 - Kadir, M.F.Z.; Aspanut, Z.; Yahya, R.; Arof, Abdul Kariem (Springer Verlag (Germany), 2011)
The polymer electrolyte membrane in this work was prepared using the solution casting technique. The polymer host is a blend of chitosan and polyethylene oxide. The solution of the blend was added with ammonium nitrate (NH 4NO 3) to supply the charge carriers for ionic conduction. From X-ray diffraction and scanning electron microscopy image, it can be inferred that the film of the 3 : 2 chitosan-polyethylene oxide blend is the most amorphous and suitable to serve as polymer host. The sample containing 40 wt-%NH 4NO 3 exhibited the highest room temperature conductivity of 1.02×10 -4 S cm -1. The salted samples were also characterised using X-ray diffraction and scanning electron microscopy in order to establish conductivity variation with different salt contents. © W. S. Maney & Son Ltd. 2011.